Aberrant accumulation of Dickkopf 4 promotes tumor progression via forming the immune suppressive microenvironment in gastrointestinal stromal tumor. (29th July 2019) - Wang, Ming; Ni, Bo; Zhuang, Chun; Zhao, Wen‐Yi; Tu, Lin; Ma, Xin‐Li; Yang, Lin‐Xi; Zhang, Zhi‐Gang; Cao, Hui
Abstract: Background: Drug resistance and tumor recurrence are the major concerns in clinical practices of gastrointestinal stromal tumor (GIST), with the urgent requirement for exploring undiscovered pathways driving malignancy. To deal with these, recent studies have made many efforts to explore prognosis indicators and establish potential therapeutic targets. Methods: Expression profiles of different risks of GISTs were described and abundant clinical evidences supported our findings in this study. Following exploration in vitro by cell experiments and verification in vivo using tumor microarray were taken to elucidate the underlying mechanism, which drove the malignancy in GIST. Results: Dickkopf 4 (DKK4), as the canonical Wnt pathway antagonist, was unexpectedly and universally upregulated in high‐risk GISTs, and aberrant accumulation of DKK4 was closely correlated with poor prognosis. In addition, tumor‐derived DKK4 could decrease immune cells infiltration and activation in the tumor microenvironment, which decreased the antitumor effects in return. And this phenomenon was recurrent in human tumor specimens. Conclusions: Our findings identified DKK4 as a proper tumor biomarker for prognosis predicting and recurrence monitoring, and suggested a novel immune‐escape mechanism driving malignancy in GIST, which might be a potential therapeutic target to improve the effects of canonical RTK therapy and combined immunotherapy. Abstract : Our findings identified Dickkopf 4 (DKK4) as a proper tumor biomarker for prognosis predicting and recurrence monitoring, and suggested a novel immune‐escape mechanism driving malignancy in GIST, which might be a potential therapeutic target to improve the effects of canonical RTK therapy and combined immunotherapy.